Localization algorithms and strategies for wireless sensor networks - Mao, Guoqiang 1974-; Fidan, Baris (Gale virtual reference library, 2009)
Provides comprehensive coverage of topics and fundamental theories underpinning measurement techniques and localization algorithms.